19 years outcome after cementless total hip arthroplasty with spongy metal structured implants in patients younger than 65 years. Issue 1 (December 2016) - Gerdesmeyer, Ludger; Al Muderis, Munjed; Gollwitzer, Hans; Harrasser, Norbert; Stukenberg, Martin; Clifford, Maria-Angela; Toepfer, Andreas
Abstract Background Cementless fixation of total hip arthroplasties (THAs) is often favored in young, high-demanding patients due to the conservation of valuable bone-stock and easier revision if loosening has occurred. Long-term outcome data of the spongy metal structured implant used in the present study in patients younger than 65 years are still lacking. Methods We conducted a retrospective chart review and functional investigation (Merle d'Aubigné score, SF-12) of patients younger than 65 years at implantation treated with a spongy metal structured THA (n = 79) from one orthopedic university center from 1985 to 1989. Results At a 19-year mean follow-up (range: 15.3 – 21.3 years), the overall stem survival rate was 93.7 %, and the overall cup survival rate was 82.3 %. Revision surgeries of the stem were performed in all cases for aseptic loosening at an average of 15.3 ± 3.5 years after implantation. Acetabular components were revised for aseptic loosening and recurrent dislocation after inlay revision on an average of 11.8 ± 4.7 years after implantation. No other device related complications occurred within the 19-year follow-up period. No correlation was found between time of revision and gender or age. Clinical outcome scores (Merle d'Aubigné score, SF-12) revealed excellent to good results of the implanted THAs in 87 % of patients. Conclusions We conclude that spongy metal structured cementless THAs implanted in young patients have an excellent survival and provide trustworthy clinical results at 19 years of follow-up.